Temperature Field-Assisted Ultraviolet Nanosecond Pulse Laser Processing of Polyethylene Terephthalate (PET) Film - Jun Xu (MDPI AG, 2021)
Understanding the mechanism of and how to improve the laser processing of polymer films have been important issues since the advent of the procedure. Due to the important role of a photothermal mechanism in the laser ablation of polymer films, especially in transparent polymer films, it is both important and effective to adjust the evolution of heat and temperature in time and space during laser processing by simply adjusting the ambient environment so as to improve and understand the mechanism of this procedure. In this work, studies on the pyrolysis of PET film and on temperature field-assisted ultraviolet nanosecond (UV-ns) pulse laser processing of polyethylene terephthalate (PET) film were performed to investigate the photothermal ablation mechanism and the effects of temperature on laser processing. The results showed that the UV-ns laser processing of PET film was dominated by the photothermal process, in which PET polymer chains decomposed, melted, recomposed and reacted with the ambient gases. The ambient temperature changed the heat transfer and temperature distribution in the laser processing. Low ambient temperature reduced the thermal effect and an increase in ambient temperature improved its efficiency (kerf width: 39.63 μm at −25 °C; 48.30 μm at 0 °C; 45.81 μm at 25 °C; 100.70 μm at 100 °C) but exacerbated the thermal effect.